Geographical Distribution of Iron Redox Cycling Bacterial Community in Peatlands: Distinct Assemble Mechanism Across Environmental Gradient - Yang, Liang; Jiang, Ming; Zou, Yuanchun; Qin, Lei; Chen, Yingyi (Frontiers in Microbiology, 2021)
Microbial-mediated iron (Fe) oxidation and reduction greatly contribute to the biogeochemistry and mineralogy of ecosystems. However, knowledge regarding the composition and distribution patterns of iron redox cycling bacteria in peatlands remains incomplete. Here, using high-throughput sequencing, we compared iron redox cycling bacterial community biogeographic patterns and assemblies between soil and water samples obtained from different types of peatland across four regions of Northeast China. A total of 48 phylotypes were identified as potential iron redox bacteria, which had higher than 97% similarity with Fe(II)-oxidizing bacteria (FeOB) and Fe(III)-reducing bacteria (FeRB), respectively. Among them, Rhodoferax, Clostridium, Geothrix, Sideroxydans, Geobacter, Desulfovibrio, and Leptothrix could be used as bioindicators in peatlands for characterizing different hydrological conditions and nutrient demands. Across all samples, bacterial communities associated with iron redox cycling were mainly affected by pH, DOC, and Fe2+. Distance-decay relationship (DDR) analysis indicated that iron redox cycling bacterial communities in soil, but not in water, were highly correlated with geographic distance. Additionally, null model analysis revealed that stochastic processes substituted deterministic processes from minerotrophic fens to ombrotrophic bogs in soils, whereas deterministic processes were dominant in water. Overall, these observations suggested that bacteria involved in iron redox cycling are widespread in diverse habitats and exhibit distinct patterns of distribution and community assembly mechanisms between soil and water in peatlands.